PERANAN CSR PT. ARUN NGL DALAM PENGEMBANGAN UKM DI ACEH UTARA - Muhammad Yusrilsya; Kasyful Mahalli (Departemen Ekonomi Pembangunan USU, 2013)
This research is as a mean to know the role program the CSR PT.Arun cover-ing public participation, aid of capital UKM, aid of partner of product promotion, partner aid construck the environment and aid of education and training UKM in de-velopment in 12 country side of Muara Batu subdistrict the north regency Aceh, either through simultan and also by parsial. Population in this research is importance con-sumer (stakeholders) patternprogram the CSR which cooperation, that is cover the division / unit of organizer CSR, Governmental, College, other LSM Institutand also UKM which is gone the round of in region of north regency Aceh Governance. Sum up the population in this research as much 488 stakeholder. By using approach of purposive of sampling or election in intent with the certain consideration, got by as much 78 stakeholder to be made by as responder in this research everyone of division / unit of organizer of CSR PT.Arun NGL as much 6 people, perpetrator UKM as much 10 people, deputizing governance (countryside, subdistrict, regency, province) as much 21 orang, deputizing college (expert, observer, academician) as much 24 people and society (local, productive age, LSM) As much 17 people. Especial data used in this research is primary data that is data mustered by passing quesioner research. Data which have been gathered hereinafter descriptive statistical dianlisis and statis-tical analysis method of inferensial covering : test of validity and reliabilitas, test the classic assumption, pemodelan, analisi of coefficient determinasi (R2), Test the statis-tical F for the examination of hipotesi by simultan and test the statistical t for the ex-amination of hypothesis by parsial. Pursuant to result analyse, concluded by that pro-gram the CSR PT.Arun NGL covering public participation, aid of capital UKM, aid of partner of product promotion, partner aid construct the environment and aid of edu-cation and training of UKM of sharingsignifikan in development UKM 12 countryside in Muara Batu subdistrict the north regency Aceh, either through simultan and also by parsial, ceteris paribus.Keywords : CSR Program and Economic Expansion